Analysis of gonadotropin releasing hormone receptor gene (GnRHR) expression map in digestive system of Hu sheep - ZHANG Wei; ZHANG Jun-sheng; ZHANG Yao; WANG Li-hong (浙江大学学报. 农业与生命科学版, 2012)
To detect the gonadotropin releasing hormone receptor (GnRHR) mRNA expression pattern in sheep's digestive system, the SYBR green real-time fluorescence quantitative polymerase chain reaction (RT-PCR) method was established. With this method, the GnRHR mRNA expression in stomach and intestinum system of Hu sheep was detected. The results showed that GnRHR mRNA expressions were detected in rumen, reticulum, omasum, abomasums, duodenum, jejunum, ileum, caecum, colon and rectum. The GnRHR mRNA expression in rumen was significantly higher than those in other tissues (P<0.01); the expression in reticulum was significantly higher than that in duodenum (P<0.01) and higher than those in omasum, caecum and rectum (P<0.05); the expression in abomasums was significantly higher than those in omasum, jejunum, ileum and caecum (P<0.01), and higher than those in colon, rectum (P<0.05); the expression in colon was higher than those in duodenum and rectum (P<0.05). It is demonstrated that there are GnRHR mRNA expressions in the digestive system of Hu sheep. It provides new evidences for the research field of GnRH functional diversity.